The peculiarities of financing higher education in Russia and abroad - N. I. Skvortsov; S. Ye. Demidova (Путеводитель предпринимателя)
The relevance of the research is determined by the need to improve the mechanisms of management and financing of higher education in Russia in the context of the introduction of new educational standards and the intensification of market relations in this area. The purpose of the work is to substantiate the directions of modernization of financial support for higher education, aimed at increasing its competitiveness and meeting the needs of the economy. The scientific significance lies in the systematization of factors affecting the effectiveness of the use of budgetary and extra–budgetary funds by universities. The practical value lies in the possibility of choosing different approaches to financing that take into account the specifics of educational institutions. The main results of the work show that, despite the high rates of population enrollment in tertiary education in Russia, government spending on higher education remains at an average level compared with the OECD countries. The paper identifies the problems associated with the predominance of regulatory per capita financing, and suggests ways to increase the efficiency of using financial resources. The scientific novelty lies in the justification of the need to differentiate government subsidies and programs, taking into account the priorities and quality of educational programs. A model of «flexible financing» is proposed that integrates public and private resources, an «educational contract» mechanism, and regional coefficients for a balanced allocation of funds.